특수학교 고교학점제의 선택과목에 대한 중등과정 학부모의 인식과 요구 - 손지영(Son, Jiyoung); 조영희(Cho, Younghee) (특수교육논총, 2024)
연구목적: 본 연구에서는 특수학교 중등과정 학부모를 대상으로 고교학점제와 선택과목에 대한 인식을 조사하여 이들의 요구를 반영한 장애학생 맞춤형 교육과정을 구현하는 고교학점제 개선 방향을 도출하고자 하였다. 연구방법: 이에 전국의 기본 교육과정 운영 특수학교 중등과정에 재학 중인 총 374명의 학부모가 설문조사에 참여하였다. 설문조사의 척도형 문항은 기술통계 분석을 실시하였고 기입형 문항은 빈도분석을 실시하였으며, 개방형 응답에 대한 자료 분석은 응답 내용에서 키워드를 추출하여 범주화하는 질적 분석을 실시하였다. 연구결과: 첫째, 특수학교 학부모의 고교학점제에 대한 이해 정도는 높은 수준이 아니었으며, 고교학점제의 장점은 장애 특성에 적합한 맞춤형 진로지도 제공으로 인식하였다. 둘째, 다수의 학부모는 사회성 및 대인관계 등의 일상생활기술과 다양한 직업기술 관련 과목들이 특수학교에 필요한 선택과목으로 인식하였으며, 장애 특성을 고려한 선택과목들이 개발되기를 원하였다. 또한 특수학교에서 선택과목 운영을 위해 전문강사 지원과 지역사회 교육기관과의 협력 지원이 필요하다는 의견이 높게 나타났다. 결론: 2025년의 고교학점제 전면 도입을 대비하여 학교 공동체의 구성원으로서 학부모의 요구를 토대로 특수학교 고교학점제의 방향성을 명료화하였고 특수교육 기본 교육과정의 교과목을 지속적으로 개선해 나갈 수 있는 교육적 시사점을 도출하였다. Purpose: This study investigated the perception of high school credit systems and elective subjects among parents of middle and high school students in special schools and attempted to derive directions for improving the high school credit system by implementing a customized curriculum for students with disabilities. Methods: A total of 374 parents of middle and high school students in special schools operating a basic curriculum across the country participated in the survey. Descriptive statistics and frequency analyses were conducted on the survey questions, and a qualitative analysis was conducted on the open-ended responses. Results: First, the level of understanding of the high school credit system among special school parents was generally low, and they generally recognized the advantage of the high school credit system in providing customized career guidance that is appropriate for the characteristics of specific disabilities. Second, parents want subjects related to daily life and various vocational skills as subjects required as electives in special schools, and they want elective subjects that consider the characteristics of disabilities to be developed. Additionally, parents' need to support professional instructors and cooperate with community educational institutions for elective subjects in special schools. Conclusion: In preparation for the full introduction of the high school credit system in 2025, the direction of the high school credit system for special schools was clarified based on the demands of parents as members of the school community. Additionally, educational implications for continuously improving the subjects of the basic special education curriculum were derived. KCI Citation Count: 0